The high impact of using multimedia in enhancing education in schools - Badi, Hana J.; Zeki, Akram M. (IIUM Press, 2015)
Educating children by using the right and appropriate way is one of the important thing that we should take care of. Traditional way of teaching is no longer useful or enough to deliver information to the students nowadays. That happens due to the new technologies coming up each day of our life. Enhancing education by using new technologies is one solution to provide better understanding for students and more comfort for teachers.